2022
DOI: 10.3389/fcimb.2022.853981
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota: Therapeutic Targets of Ginseng Against Multiple Disorders and Ginsenoside Transformation

Abstract: Panax ginseng, as the king of Chinese herb, has significant therapeutic effects on obesity, type 2 diabetes mellitus, fatty liver disease, colitis, diarrhea, and many other diseases. This review systematically summarized recent findings, which show that ginseng plays its role by regulating gut microbiota diversity, and gut microbiota could also regulate the transformation of ginsenosides. We conclude the characteristics of ginseng in regulating gut microbiota, as the potential targets to prevent and treat meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 122 publications
1
33
0
Order By: Relevance
“…exhibited converting activity of ginsenosides Rb1, Rb2, and Rc to compound K [ 145 ]. According to a recent literature review, the main gut microbial genera involved in ginsenoside biotransformation are Bacteroides , Bifidobacterium , and Eubacterium [ 205 ].…”
Section: Resultsmentioning
confidence: 99%
“…exhibited converting activity of ginsenosides Rb1, Rb2, and Rc to compound K [ 145 ]. According to a recent literature review, the main gut microbial genera involved in ginsenoside biotransformation are Bacteroides , Bifidobacterium , and Eubacterium [ 205 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other drugs, TCM has many advantages, including low toxicity, fewer side effects, and less risk of drug resistance ( 54 ). It has been reported that Radix Puerariae extract can treat alcoholic liver disease by improving alcohol-induced intestinal barrier dysfunction, and Panax ginseng C. A. Meyer extract can treat non-alcoholic fatty liver disease by regulating intestinal flora ( 26 , 55 ). Rhubarb extract pretreatment can improve alcohol-induced ALI in mice by improving intestinal homeostasis and restoring intestinal barrier function, especially by increasing the relative abundance of Akkermansia muciniphila in cecal contents, which is considered to be a potential probiotic ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have now demonstrated the therapeutic effects of TCM in cancer, cardiovascular disease, inflammation, and liver disease (19)(20)(21)(22). Some low-toxic Chinese herbs, such as Salvia miltiorrhiza, licorice, Radix Puerariae, and Panax ginseng C. A. Meyer, contain a variety of active ingredients such as terpenoids, flavonoids, alkaloids, phenols, polysaccharides, and other active ingredients, which can play a strong role in anti-inflammation and antioxidation, improve the immune function of the body, and regulate intestinal flora (23)(24)(25)(26). Puerarin is a bioactive flavone isolated from Puerariae Lobatae Radix (gegen), an herbal TCM used for many pathological conditions; Curcumin is the main ingredient of Curcuma longa L., commonly known as turmeric (jianghuang), a plant of high medicinal values and widely used especially in Southeast Asia; Ginsenosides are saponins, which are the major pharmacologically active components of Panax Ginseng (renshen).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are a kind of bioactive components extracted from plant medicine Ginseng. Ginsenosides can fight a variety of diseases through intestinal flora (97). Ginsenoside Rg1 can relieve T2D symptoms induced by HFD and streptozotocin (STZ) in rats, which may be related to the increase of the proportion of lactic acid bacteria and Lachnospiraceae and the decrease of the proportion of Lactobacillus by Rg1.…”
Section: Individual Herbs or Herbal Extractsmentioning
confidence: 99%